2012
DOI: 10.1039/c2ob26300a
|View full text |Cite
|
Sign up to set email alerts
|

DABCO and Bu3P catalyzed [4 + 2] and [3 + 2] cycloadditions of 3-acyl-2H-chromen-ones and ethyl 2,3-butadienoate

Abstract: DABCO-catalyzed [4 + 2] and Bu(3)P-catalyzed [3 + 2] cycloadditions between 3-acyl-2H-chromen-ones and ethyl 2,3-butadienoate were developed for the synthesis of dihydropyran-fused and cyclopenten-fused chromen-2-ones with high regio- and stereo-selectivities, respectively. The synthetic procedures have the advantages of mild reaction conditions, convenient handling and good atom economy as well as a wide substrate scope, which make this method useful for the synthesis of potentially biologically active dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Obtained as a white solid; mp: 137-138 • C (lit (Specht, Martic & Farid, 1982) 137-139 • C); IR (cm −1 ): 3408, 1714, 1657, 1609, 1567; 1 H-NMR (CDCl 3 , 500 MHz) δ 8.09 (s, 1H), 7.90 (d, J = 7.23 Hz, 2H), 7.67-7.60 (m, 3H), 7.49 (t, J = 7.1 Hz, 2H), 7.42 (d, J = 8.1 Hz, 1H), 7.36 (t, J = 7.2 Hz, 1H) ppm; 13 C{ 1 H}-NMR (CDCl 3 , 101 MHz) δ 191.8 (C), 158.5 (C), 154.9 (C), 145.6 (CH), 136.3 (C), 134.0 (CH), 133.8 (CH), 129.7 (CH), 129.3 (CH), 128.7 (CH), 127.2 (C), 125.1 (CH), 118.3 (C), 117.1 (CH) ppm. 3-Benzoyl-6-bromo-2H -chromen-2-one (12b); (Wang et al, 2012) (24 h, 465 mg, 47%). Obtained as a white solid; mp: 171-176 • C (lit (Wang et al, 2012) 171-172 • C); IR (cm −1 ): 3413, 3069, 1717, 1656, 1619, 1598; 1 H-NMR (CDCl 3 , 500 MHz) δ 7.97 (s, 1H), 7.87 (d, J = 7.43 Hz, 2H), 7.72 (d, J = 7.13 Hz, 2H), 7.63 (t, J = 7 Hz, 1H), 7.49 (t, J = 7.4 Hz, 2H), 7.30 (d, J = 9.06 Hz, 1H) ppm; 13 C{ 1 H}-NMR (CDCl 3 , 101 MHz) δ 191.2 (C), 157.8 (C), 153.6 (C), 143.9 (CH), 136.4 (CH), 136.0 (C), 134.2 (CH), 131.4 (CH), 129.7 (CH), 128.8 (CH), 128.2 (C), 119.8 (C), 118.8 (CH), 117.7 (C) ppm.…”
Section: Synthesis Of 3-carbonylcoumarins (12a-d)mentioning
confidence: 99%
See 1 more Smart Citation
“…Obtained as a white solid; mp: 137-138 • C (lit (Specht, Martic & Farid, 1982) 137-139 • C); IR (cm −1 ): 3408, 1714, 1657, 1609, 1567; 1 H-NMR (CDCl 3 , 500 MHz) δ 8.09 (s, 1H), 7.90 (d, J = 7.23 Hz, 2H), 7.67-7.60 (m, 3H), 7.49 (t, J = 7.1 Hz, 2H), 7.42 (d, J = 8.1 Hz, 1H), 7.36 (t, J = 7.2 Hz, 1H) ppm; 13 C{ 1 H}-NMR (CDCl 3 , 101 MHz) δ 191.8 (C), 158.5 (C), 154.9 (C), 145.6 (CH), 136.3 (C), 134.0 (CH), 133.8 (CH), 129.7 (CH), 129.3 (CH), 128.7 (CH), 127.2 (C), 125.1 (CH), 118.3 (C), 117.1 (CH) ppm. 3-Benzoyl-6-bromo-2H -chromen-2-one (12b); (Wang et al, 2012) (24 h, 465 mg, 47%). Obtained as a white solid; mp: 171-176 • C (lit (Wang et al, 2012) 171-172 • C); IR (cm −1 ): 3413, 3069, 1717, 1656, 1619, 1598; 1 H-NMR (CDCl 3 , 500 MHz) δ 7.97 (s, 1H), 7.87 (d, J = 7.43 Hz, 2H), 7.72 (d, J = 7.13 Hz, 2H), 7.63 (t, J = 7 Hz, 1H), 7.49 (t, J = 7.4 Hz, 2H), 7.30 (d, J = 9.06 Hz, 1H) ppm; 13 C{ 1 H}-NMR (CDCl 3 , 101 MHz) δ 191.2 (C), 157.8 (C), 153.6 (C), 143.9 (CH), 136.4 (CH), 136.0 (C), 134.2 (CH), 131.4 (CH), 129.7 (CH), 128.8 (CH), 128.2 (C), 119.8 (C), 118.8 (CH), 117.7 (C) ppm.…”
Section: Synthesis Of 3-carbonylcoumarins (12a-d)mentioning
confidence: 99%
“…3-Benzoyl-6-bromo-2H -chromen-2-one (12b); (Wang et al, 2012) (24 h, 465 mg, 47%). Obtained as a white solid; mp: 171-176 • C (lit (Wang et al, 2012) 171-172 • C); IR (cm −1 ): 3413, 3069, 1717, 1656, 1619, 1598; 1 H-NMR (CDCl 3 , 500 MHz) δ 7.97 (s, 1H), 7.87 (d, J = 7.43 Hz, 2H), 7.72 (d, J = 7.13 Hz, 2H), 7.63 (t, J = 7 Hz, 1H), 7.49 (t, J = 7.4 Hz, 2H), 7.30 (d, J = 9.06 Hz, 1H) ppm; 13 C{ 1 H}-NMR (CDCl 3 , 101 MHz) δ 191.2 (C), 157.8 (C), 153.6 (C), 143.9 (CH), 136.4 (CH), 136.0 (C), 134.2 (CH), 131.4 (CH), 129.7 (CH), 128.8 (CH), 128.2 (C), 119.8 (C), 118.8 (CH), 117.7 (C) ppm. 3-Acetyl-6-bromo-2H -chromen-2-one (12c); (Parveen, Khan & Ahmed, 2019) (24 h, 360 mg, 45%).…”
Section: Synthesis Of 3-carbonylcoumarins (12a-d)mentioning
confidence: 99%
“…Allene derivatives including allene ketones, allenoates, and arylallenes are available as the building blocks in the synthesis of many natural products . Noteworthy, the [2+4] cyclizations of allene derivatives with various reacting partners are extremely useful for the construction of O‐, N‐ and S‐containing heterocycles, which have been widely employed in the synthesis field of natural products with special biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey revealed that reaction of chiral phosphine with various substrates like activated alkene, allenes and alkynes lead to formation of optically active carbo‐ and heterocycles . Recently, Wang's and co‐workers have described the formtion of an unexpected product via DABCO and Bu 3 P catalyzed [4+2] and [3+2] cycloadditions reaction of 3‐acyl‐2 H ‐chromen‐ones (Scheme , Entry a). Xiao's sp 3 C−H Functionalization of 2‐methylpyridine and coumarin‐3‐carboxylic Acids followed by decarboxylation reaction (Scheme , Entry b) and Lin's unexpected α‐Addition of α,β‐unsaturated γ‐butyrolactams to coumarin derivatives catalyzed by DABCO in THF (Scheme , Entry c) also has been reported.…”
Section: Introductionmentioning
confidence: 99%